Case Report: Complete pathologic response in advanced melanoma with SFRT and dual checkpoint inhibition - Hobson, Jared; Grams, Michael P.; Gicobi, Joanina K.; Wigle, Dennis; Kottschade, Lisa A.; Durham, Lindsey A.; Corbin, Kimberly; Dong, Haidong; Markovic, Svetomir N.; Park, Sean S. (Frontiers in Oncology, 2025)
Immune checkpoint inhibitors (ICIs) have transformed the treatment landscape for advanced melanoma, though response rates remain limited in bulky disease. Herein, we report the case of a complete pathologic response following combination spatially fractionated radiation therapy (SFRT) and dual nivolumab and ipilimumab for a 12 cm right lung melanoma mass, with subsequent lobectomy revealing no viable tumor cells. Now disease free 2.5 years after treatment, including more than 1 year off all systemic therapy, this case highlights the potential synergy between SFRT and immunotherapy in advanced melanoma management.